Prevention and control of avian influenza virus: Recent advances in diagnostic technologies and surveillance strategies - Qian Niu; Zhiwen Jiang; Lifang Wang; Xiang Ji; Guy Baele; Ying Qin; Liyan Lin; Alexander Lai; Ye Chen; Michael Veit; Shuo Su (Nature Communications)
The natural host for avian influenza virus (AIV) is waterfowl. However, certain subtypes have breached species barriers, causing epizootics in many avian and mammalian species with occasional zoonotic infections in humans. The ongoing spread of highly pathogenic avian influenza (HPAI) A(H5N1) poses a significant and growing public health threat. Here, we discuss recent advances in viral detection and characterization technologies and their integration into the diagnostics and surveillance of AIV within a “One Health” framework.